Managing Character Education in Pluralistic Schools: A Model of Internalization of Interfaith Values - Mashoedi, Mashoedi; Munif, Muhammad; Suhermanto, Suhermanto (Al-Qalam Institue, 2025)
This study aims to analyze the implications of internalizing religious values in enhancing character management in a public elementary school with religious diversity. The research employed a descriptive qualitative approach, using observations, interviews, and documentation involving teachers, students, and school staff. Data analysis was conducted thematically to explore internalization strategies and their impacts on students’ religious character development. The findings highlight that strategies like greeting others, collective prayers, and regular congregational prayers effectively instill religious values inclusively. Teachers’ role modeling through activities like home visits and donations fosters empathy and solidarity across religions. Reward and punishment mechanisms enhance moral awareness and intrinsic motivation. Christian students benefit from tailored activities, such as morning prayers and memorizing Bible verses, which promote tolerance. Overall, the internalization of religious values in a multi-faith school environment contributes to students’ moral, spiritual, and social development. The implications of this study for educational management emphasize the importance of integrating interfaith value internalization into character education programs. School leaders and educators should adopt inclusive strategies, such as role modeling, structured religious activities, and reward mechanisms, to foster moral, spiritual, and social development, thereby ensuring a harmonious learning environment.